A place-based approach in collaborative governance - Miren Larrea; Ainhoa Arrona; Xabier Barandiaran (Oñati Socio-Legal Series)
Collaborative governance is a broad concept that includes many forms of collaborative arrangements among various actors that differ in their nature, objectives, and types of interactions. This article empirically illustrates how, despite being understudied in the literature on collaborative governance, the “place” dimension (used here to refer to territory as a collective subject) can serve as a backbone that provides a distinctive logic and dynamic, bringing about a specific collaborative governance model — one that is especially relevant in the context of collaborative initiatives by regional governments. We describe a series of necessary features for place-based dynamics to emerge. The article seeks to share a conceptual framework that distinguishes between government-centred and place-based approaches to collaborative governance which can be used as a reflective tool for facilitators of collaborative governance. The framework relies on two empirical cases employed to illustrate its application.